1998
DOI: 10.1038/sj.gt.3300775
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lysosomal storage disease in MPS VII mice using a recombinant adeno-associated virus

Abstract: Mucopolysaccharidosis type VII (MPS VII) is a lysosomalproduced low GUS activity in several tissues. This latter storage disease caused by a genetic deficiency of ␤-glucutreatment of MPS VII mice reduced glycosaminoglycan ronidase (GUS). We used a recombinant adeno-associalevels in the liver to normal and reduced storage granules ted virus vector (AAV-GUS) to deliver GUS cDNA to MPS dramatically. We show that a single administration of VII mice. The route of vector administration had a dramatic AAV-GUS can pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 34 publications
4
54
0
Order By: Relevance
“…Several studies have shown that AAV-mediated gene transfer corrects neuropathology and, to a lesser extent, behavioral deficits in mouse models of neurometabolic disease (21)(22)(23)(24)(25)(26)(27). However, experiments in various lysosomal storage disease mouse models (e.g., mucopolysaccharidosis VII, infantile neuronal ceroid lipofuscinosis, and Sanfilippo type IIIB disease) have been primarily restricted to AAV serotypes 1 and 2 to mediate gene transfer in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that AAV-mediated gene transfer corrects neuropathology and, to a lesser extent, behavioral deficits in mouse models of neurometabolic disease (21)(22)(23)(24)(25)(26)(27). However, experiments in various lysosomal storage disease mouse models (e.g., mucopolysaccharidosis VII, infantile neuronal ceroid lipofuscinosis, and Sanfilippo type IIIB disease) have been primarily restricted to AAV serotypes 1 and 2 to mediate gene transfer in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…They show widespread storage of GAGs in lysosomes of visceral organs, skeleton, and brain. The murine model of MPS VII has been widely used for evaluating the effectiveness of bone marrow transplantation (10)(11)(12)(13)(14), enzyme replacement (15)(16)(17)(18)(19)(20)(21)(22), and gene therapy with retroviral (23)(24)(25)(26)(27)(28), adenoviral (29 -33), and adenoassociated viral vectors (34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…The exciting potential of AAV-mediated gene delivery to meet this challenge is substantiated by data generated in over 40 studies in animal models involving at least 15 different LSD phenotypes. The most extensively investigated phenotypes are GSD II [40][41][42][43][44][45][46] and MPS VII [47][48][49][50][51][52][53][54] and distillation of data obtained for these conditions provides representative insights across the spectrum of LSDs.…”
Section: Lysosomal Storage Diseasesmentioning
confidence: 99%
“…Initial studies of phenotype correction in the mouse using AAV vectors, performed in the late 1990s, focused on systemic delivery of enzyme by either direct intramuscular or intravenous injection. 47,48 While intramuscular injection resulted in high localized enzyme production, cross-correction of other tissues was limited, probably as a consequence of inadequate local secretion and distal tissue uptake. Intravenous delivery resulted in measurable enzyme levels in a number of tissues, most notably the liver in which glycosaminoglycan levels were normalized with an associated dramatic drop in storage granules.…”
Section: Lysosomal Storage Diseasesmentioning
confidence: 99%